Evaluative Study: Implementation of the Independent Curriculum in Improving the Quality of the Learning Process and Student Learning Outcomes in Elementary Schools - Agung Setyawan; Azkia Najwa Rosyadi; Shelvi Eka Nur Anggraeni (Examinations: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
The education system in Indonesia places a larger allocation of teaching than the allocation of education. So that educational activities are more emphasized on the process of improving abilities, skills, and intelligence alone. Meanwhile, the formation of superior, cultured, and quality characteristics has not been fully concentrated in a fundamental way. This situation has resulted in the emergence of various educational problems that are not properly addressed. So it is worrying that it will affect various efforts to improve the quality of education. The causes of the low quality of education in Indonesia in general include the issue of effectiveness, efficiency, and standardization of teaching. The Independent Curriculum is one of the government's initiatives in improving the quality of education by giving schools the freedom to design ideas, models, and learning assessments in accordance with the characteristics of the local environment, culture, and issues around the school environment.